Implementasi kurikulum merdeka belajar di sekolah penggerak SMP Negeri 3 Picung, kecamatan Picung-Pandeglang, Banten - Jumadi; Risma Rahmawati; Siti Maulidia Ulfah; Yayan Sudrajat (Asosiasi Dosen Pemerhati Pendidikan Indonesia, 2023)
This study aims to find out the Implementation of the Independent Curriculum at SMPN 3 Picung, Pandeglang Regency as a driving school, which since July 2022 for the 2022/2023 academic year has started implementing the Independent Curriculum. The method used in this study is a qualitative method with interview and observation research instruments. This study provides an explanation and description of the implementation of the independent curriculum in the driving schools of SMPN 3 Picung which is currently being implemented at the 7th grade level. The results of this study indicate that the implementation of the independent curriculum in the driving schools of SMPN 3 Picung has been implemented optimally and is ongoing, although In implementation there are still shortcomings and obstacles. The key to the success of implementing an independent curriculum in schools is collaboration between school principals and teachers as a community of practitioners to want to be moved, move and mobilize so that changes in learning and learning outcomes can be realized in schools.